Meditation for Quality Improvement of Medical Encounters: Single-Intervention, Vedanta-Based Meditation Effects on Vital Signs and Mood Indices - Jayaram Srinivasan MD, MPH; Patrick J. Breheny PhD (SAGE Publishing, 2012)
A 15-minute, single-intervention, individually guided, Vedanta-based meditation was evaluated for acute effects on vital signs and mood indices. This study included 99 volunteers. Subjects were led in meditations incorporating breathing techniques, relaxation exercises, mental imagery, and silent mantra repetition. Pre- and post-intervention vital signs and mood indices were assessed, including heart rate, respiratory rate, blood pressure, temperature, Beck Depression Inventory (BDI), and Likert scales for mood. The meditation was shown to have statistically significant effects in the immediate improvement of vital signs and mood indices. The most substantial effects occurred for blood pressure, respiratory rate, Beck Depression Inventory, depression, anxiousness, happiness, and peacefulness. Also, males experienced greater physiological benefit whereas females experienced greater psychological benefit. The results of this study could be useful in developing gender-specific meditations to improve vital signs and mood indices in acute settings.